EXTH-26. MICROGLIA-SPECIFIC DISRUPTION OF SIALIC ACID-SIGLEC-9/E INTERACTIONS: A NOVEL IMMUNOTHERAPY AGAINST GLIOBLASTOMA?. (14th November 2022) - Schmassmann, Philip; Roux, Julien; Tatari, Nazanin; Martins, Tomas A; Ritz, Marie-Françoise; Shekarian, Tala; Laeubli, Heinz; Hutter, Gregor
Abstract: Recently, 'don't eat me'-signals like CD47 have emerged as novel innate immune checkpoints, enabling cancer cells to evade clearance by phagocytes such as microglia (MG) or monocyte-derived cells (MdCs). Here, we aim at defining the role of inhibitory Siglec-9 in human and its mouse homologue Siglec-E in innate-centered immunotherapy against GBM. TCGA RNA-sequencing data revealed a significant correlation between high expression of immunoinhibitory SIGLEC9 and poor survival in GBM patients (log-rank p = 0.02). Using a CT-2A orthotopic GBM mouse model with MG-specific spatio-temporal deletion of Siglece (Sall1CreERT2 x Sigleceflox ), we observed high MG-proliferation upon Siglece knockout (Ki-67+ MG 14.8% in Cre neg vs. 34.9% in Cre pos p < 0.0001) accompanied by an enhanced microglial GBM-cell uptake (5.6% in Cre neg vs. 12.3% in Cre pos, p < 0.001). By extending the Siglece knockout to the MdC compartment (Cx3cr1 CreERT2 x Siglece flox ) we observed a significantly prolonged survival in the Cre pos population (21d in Cre neg vs. 27d post-tumor injection in Cre pos, p = 0.018), which could be further promoted by combining Siglece knockout with CD47 blockade (11% long-term remission in Cre pos + anti-CD47). Proteomics analysis revealed increased antigen processing and presentation capabilities of Siglece KO MdCs which was confirmed by ex-vivo OT-1 cross-presentation assays. This increased T cell priming upon MdC Siglece KO was further boosted by addition of anti-PD1 antibody to the Siglece KO + anti-CD47 combination. Resulting in 23% of animals experiencing long-term remission in the triple treatment arm, even after tumor re-challenge. Genetic targeting of sialic acids, the ligand for Siglec receptors, on CT-2A cells (GNE-KO), resulted in increased GBM-cell phagocytosis by MG and MdCs and less exhausted tumor-infiltrating CD8+ T cells (14.8% in WT vs. 5.9% in GNE-KO, p = 0.003). In a translational approach, we are currently testing anti-Siglec-9 treatment regimens in patient GBM explants, cultured for 5 days in perfusion bioreactors.